Towards functional spin-echo BOLD line-scanning in humans at 7T - Raimondo, Luisa; Heij, Jurjen; Knapen, Tomas; Dumoulin, Serge O.; van der Zwaag, Wietske; Siero, Jeroen C. W. (Magnetic Resonance Materials in Physics, Biology and Medicine, 2023)
Neurons cluster into sub-millimeter spatial structures and neural activity occurs at millisecond resolutions; hence, ultimately, high spatial and high temporal resolutions are required for functional MRI. In this work, we implemented a spin-echo line-scanning (SELINE) sequence to use in high spatial and temporal resolution fMRI.